Assessment Health Status of Healthcare Providers who work in Radiation Departments - Ayat Ibrahim Marhab, Wissam Jabbar Kassim (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Exposure to radiation is becoming a long-term public health issue. Ionizing radiation is a pervasive threat to the lives of everyone on Earth. It’s important to keep radiation doses as low as possible, even though the risk of long-term effects is extremely low. AIMS: Assess health status of healthcare providers who work in radiation departments., and to find out the differences between radiation exposure and health status of health care providers . Methodology: The cross-sectional study is conducted throughout the period of (May 10th to August 25th,2021,) in order to assess health status of healthcare providers who work in radiation departments. Purposive sample of (120) healthcare providers were selected from five hospitals in medical city complex. The sample was collected by uses the instruments which consist of two parts: Th Part 1: Healthcare providers’ general information, part2: Assessment of health status of healthcare providers : questionnaire validity the instrument was presented to 16 experts in different fields of Nursing to make it more valid. The internal consist reliability determine by crohnpach Alpha correlation which was r=0.82 for health status. Data are analyzed through the application of descriptive statistical data analysis approach that includes, frequencies, percentages, mean of scores, and inferential statistics include which include ANOVA. Results: healthcare providers are showing poor level of physical health as seen among 59.2% of them and 40.8% are showing fair level of physical health, and there are high significant differences in acute exposure to radiation with regard to physical health, psychological health, and emotional health at p-value= 0.002, 0.001, and 0.001. conclusion: The study concluded that more than half of health care provider have poor physical health ,more than half of health care provider have fair level of social role as part of their health status, more than half of health care providers have the poor psychological status